Laparoscopic versus Open Inguinal Hernia Repair in Aging Patients: A Propensity Score Matching-Based Retrospective Study - Xu Z; Zhao Y; Fu X; Hu W; Zhao C; Ge C; Ye H; Chen C (Dove Medical Press, 2023)
Zipeng Xu,1,* Yong Zhao,2,* Xu Fu,3,* Weidong Hu,1 Chunlong Zhao,1 Chen Ge,1 Hui Ye,4,5 Chaobo Chen1,3,5 1Department of General Surgery, Xishan People's Hospital of Wuxi City, Wuxi, 214105, People's Republic of China; 2Department of General Surgery, Wuxi Rehabilitation Hospital, Wuxi, 214007, People's Republic of China; 3Department of General Surgery, the Affiliated Drum Tower Hospital of Nanjing University Medical school, Nanjing, 210008, People's Republic of China; 4Department of Anesthesiology, ZhongDa Hospital, Southeast University, Nanjing, 210009, People's Republic of China; 5Department of Immunology, Ophthalmology & ORL, Complutense University School of Medicine, Madrid, 28040, Spain*These authors contributed equally to this workCorrespondence: Chaobo Chen; Hui Ye, Email bobo19820106@gmail.com; carciapene@126.comObjective: Although laparoscopic repair has been widely carried out and promoted due to its minimally invasive advantages, open surgery is still popular compared to elderly patients. This study aims to compare the outcomes of laparoscopic (LIHR) vs open repair of inguinal hernias (OIHR) in elderly patients.Methods: A retrospective analysis of the database was performed to identify elderly patients, from January 2021 through December 2022, who underwent surgery for an inguinal hernia. After a 1:1 propensity score matching (PSM) with a caliper of 0.1 was conducted to balance potential bias, binary logistic regressions were used for categorical and continuous outcomes.Results: After PSM, 78 pairs of elderly patients were enrolled in this study, and there were no significant differences in baseline between LIHR and OIHR groups. Compared to OIHR, univariable and multivariable logistic regression analysis showed that LIHR was independently affected for reducing intraoperative hemorrhage (OR = 0.06, 95% CI: 0.02- 0.18, P < 0.001) and shortening postoperative hospitalization time (OR = 0.29, 95% CI: 0.15- 0.57, P < 0.001) in elderly patients. Furthermore, LIHR (OR = 0.28, 95% CI: 0.14- 0.57, P < 0.001) and age (OR = 0.89, 95% CI: 0.82- 0.96, P = 0.002) were independent affecting factors for relieving postoperative pain. Meanwhile, no obvious differences were detected in postoperative complications [LIHR 7.7% (6/78) vs OIHR 14.1% (11/78), P = 0.199].Conclusion: LIHR was closely associated with reducing intraoperative hemorrhage and shortening postoperative hospitalization time. Whilst LIHR and age were independently affecting factors for relieving postoperative pain.Keywords: inguinal hernia, propensity score matching, elderly patient, laparoscopy, retrospective study